PENANAMAN NILAI-NILAI PANCASILA DALAM AKTIVITAS LITERASI SEKOLAH DASAR DI ERA DIGITAL - M. Nursi; Rini Parmila Yanti; Ashabul Khairi; Hari Adi Rahmad (Study program PGSD FKIP Universitas Bung Hatta, 2026)
The integration of Pancasila values into elementary school literacy activities is essential in strengthening national identity amidst the rapid digital transformation. This study explores how digital literacy practices in elementary schools can serve as an effective medium for instilling Pancasila values. Utilizing a qualitative descriptive approach, data were collected through classroom observations, interviews with teachers, and document analysis in five public elementary schools across West Sumatra. The findings reveal three key themes: (1) the integration of Pancasila values in thematic digital literacy activities, (2) the use of digital technologies—such as e-books, educational apps, and digital storytelling—as media for civic character education, and (3) the challenges faced by teachers, including digital competency gaps and the lack of culturally relevant digital content, along with their strategic responses. Quantitative data from surveys and observations indicate that 82% of students demonstrated increased understanding of Pancasila principles after engaging in structured digital literacy activities. This study underscores the importance of teacher readiness, digital content development, and pedagogical innovation to optimize the role of digital literacy in civic education at the elementary level.